2022
DOI: 10.3389/fenvs.2022.998915
|View full text |Cite
|
Sign up to set email alerts
|

The impact of FDI quality characteristics on carbon emission intensity: Evidence from China

Abstract: Using data from 30 provincial-level in China during 2005–2019, this paper investigates the impact of foreign direct investment (FDI) quality characteristics on carbon emission intensity. Based on the Copeland-Taylor model, the mechanism of the impact of FDI quality characteristics on carbon emission intensity is also investigated. The key findings demonstrate that FDI quality traits considerably lower regional carbon intensity, and the result is still robust after considering the spatial correlation and using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…They confirmed that FDI plays a vital role in eco-innovation to mitigate its negative environmental consequences and reduce carbon emissions (Li et al 2019). Consequently, FDI boosts the local enterprises to adopt eco-innovation practices and the demand for clean products, thereby mitigating the intensity of carbon emissions in the host countries (Ma et al 2022). Therefore, we believe that the economic environment must be transformed to attract FDI, with a two-fold goal: first, MENA countries must build an enabling environment; second, they have to support eco-innovation using taxes and public procurement to ensure climate protection and achieve SDGs target, while enhancing economic growth.…”
Section: The Dual Mediating Effect Of Fdimentioning
confidence: 87%
“…They confirmed that FDI plays a vital role in eco-innovation to mitigate its negative environmental consequences and reduce carbon emissions (Li et al 2019). Consequently, FDI boosts the local enterprises to adopt eco-innovation practices and the demand for clean products, thereby mitigating the intensity of carbon emissions in the host countries (Ma et al 2022). Therefore, we believe that the economic environment must be transformed to attract FDI, with a two-fold goal: first, MENA countries must build an enabling environment; second, they have to support eco-innovation using taxes and public procurement to ensure climate protection and achieve SDGs target, while enhancing economic growth.…”
Section: The Dual Mediating Effect Of Fdimentioning
confidence: 87%